PENGARUH LATIHAN PLYOMETRIC TERHADAP POWER OTOT TUNGKAI PADA PESERTA EKSTRAKURIKULER BOLA VOLLY DI SMAN 12 MERANGIN - Afriansyah, Dimas; Ilham; Kurniawan, Alexander (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Volleyball is a sport that requires physical abilities, especially leg muscle power, to support movements such as smashing and blocking. Leg muscle power can be improved through programmed training, one of which is plyometric training. This study aimed to determine the effect of plyometric training on improving leg muscle power of volleyball extracurricular participants at SMAN 12 Merangin. The research method used was an experimental method with a one-group pre-test and post-test design. The sample consisted of 16 participants selected using a total sampling technique. The research instrument used the vertical jump test to measure leg muscle power. The results showed that the mean pre-test score was 61.5 with a minimum of 52 and a maximum of 67, while the mean post-test score increased to 69.0 with a minimum of 62 and a maximum of 78. The normality test indicated that the data were normally distributed, and hypothesis testing using the t-test showed a significant effect of plyometric training on improving leg muscle power. It can be concluded that plyometric training has a positive and significant effect on improving leg muscle power of volleyball extracurricular participants at SMAN 12 Merangin.